Packaging technology fundamentals, materials and processes - Emblem, Anne; Emblem, Henry (Woodhead Pub., 2012)
Packaging is a complex and wide-ranging subject. Comprehensive in scope and authoritative in its coverage, Packaging technology provides the ideal introduction and reference for both students and experienced packaging professionals. Part one provides a context for the book, discussing fundamental issues relating to packaging such as its role in society and its diverse functions, the packaging supply chain and legislative, environmental and marketing issues. Part two reviews the principal packaging materials such as glass, metal, plastics, paper and paper board. It also discusses closures, adhesives and labels. The final part of the book discusses packaging processes, from design and printing to packaging machinery and line operations, as well as hazard and risk management in packaging. With its distinguished editors and expert contributors, Packaging technology is a standard text for the packaging industry. The book is designed both to meet the needs of those studying for the Diploma in Packaging Technology and to act as a comprehensive reference for packaging professionals. Provides the ideal introduction and reference for both students and experienced packaging professionalsExamines fundamental issues relating to packaging, such as its role in society, its diverse functions, the packaging supply chain and legislative, environmental and marketing issuesReviews the principal packaging materials such as glass, metal, plastics, paper and paper board.
Keywords: Packaging.; Packaging -- Great Britain.; Packaging machinery -- Great Britain.; Great Britain.; elektronické knihy; electronic books